Coadsorption of hydrogen and CO on Pt(335): Structure and vibrational Stark effect. - Tobin, Roger G.; Hong, Wang.; Lambert, David K. (Tufts University. Tisch Library., 2017)
We have studied CO and H coadsorbed on the stepped Pt(335) surface in vacuum to learn about their interaction at steps and to compare with previous electrochemical studies. Both electroreflectance and conventional reflectance absorption vibrational spectra were obtained of atop bonded CO. Its stretch vibrational frequency ν, Stark tuning rate (dν/dE), and integrated absorbance S were all studied as functions of CO and H coverage. With CO only on step edges, S for atop CO decreases to zero with increasing H coverage. The CO affected by H is in a mixed phase and is bridge bonded. Atop CO's (dν/dE) decreases with increasing CO coverage but is unaffected by coadsorbed H. In the low CO coverage limit (dν/dE)=88±9 cm−1/(V/Å), in agreement with theory and with previous measurement. The standard model of dipole-dipole screening is unable to explain the CO coverage dependence of both (dν/dE) and S. The vibrational polarizability of CO increases with coverage. We also compare our results with spectroelectrochemical data from CO on Pt(335) in aqueous electrolyte. Our measured (dν/dE) is too small to explain the variation of CO's ν with electrode potential φ in the electrochemical experiments if (dE/dφ) in the double‐layer is taken from conventional models. The effect of coadsorbed H is also different; in vacuum H has no effect on CO's (dν/dE) but in electrolyte, at low CO coverage, (dν/dφ) drops to zero at the potential where H adsorption begins.